INTERNALISASI NILAI PENDIDIKAN SOSIAL DALAM MENUMBUHKAN KEPEDULIAN SOSIAL MAHASISWA STKIP MELAWI - Deki Wibowo; Ahmad Khoiri; Waridah Waridah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2023)
Abstract: Education is a conscious effort in fostering and developing the human person both spiritually and physically. Some expert opinions define education as a kind of process for humans to change the attitudes and behaviour of an individual or group of people. The purpose of instilling value education to STKIP Melawi students is very important in shaping the personality of STKIP Melawi students, because humans have perfection and intelligence in thinking and acting (affective intelligence emotionally, socially, and spiritually). This research uses a qualitative method that is intended to describe and analyse phenomena, events, social activities, attitudes, beliefs, perceptions, thoughts of people individually or in groups in the environment of STKIP Melawi campus students. The results of the study concluded that there are three activities in the classroom that can improve the attitude of social care, namely through honesty, courtesy, and mutual respect for fellow students. In the attitude of caring students need to get used to the